A Novel BMP2‐Coprecipitated, Layer‐by‐Layer Assembled Biomimetic Calcium Phosphate Particle: A Biodegradable and Highly Efficient Osteoinducer. (4th March 2013) - Zheng, Yuanna; Wu, Gang; Liu, Tie; Liu, Yi; Wismeijer, Daniel; Liu, Yuelian
Abstract Purpose To repair large‐size bone defects, most bone‐defect‐filling materials in clinic need to obtain osteoinductivity either by mixing them with particulate autologous bone or adsorbing bone morphogenetic protein 2 (BMP2). However, both approaches encounter various limitations. In this study, we hypothesized that our novel particles of biomimetic BMP2‐coprecipitated calcium phosphate (BMP2‐cop.BioCaP) could serve as an independent and biodegradable osteoinducer to induce bone formation efficiently for these bone‐defect‐filling materials, for example, deproteinized bovine bone (DBB). Materials and Methods We alternately layer‐by‐layer assembled amorphous and crystalline CaP triply to enable a "bamboo‐like" growth of the particles. We functionalized BioCaP by coprecipitating BMP2 into the most outer layer of BioCaP. We monitored the degradation, osteoinductivity, and foreign‐body reaction of either BMP2‐cop.BioCaP or its combination with DBB in an ectopic site in rats. Results After 5 weeks, the BMP2‐cop.BioCaP significantly induced new bone formation not only alone but also when mixed with DBB. Its osteoinductive efficiency was 10‐fold higher than the adsorbed BMP2. Furthermore, BMP2‐cop.BioCaP also reduced significantly the host foreign‐body reaction to DBB in comparison with the adsorbed BMP2. After a 5‐week implantation, more than 90% of BMP2‐cop.BioCaP degraded. Conclusions These findings indicate a promising clinical potential for BMP2‐cop.BioCaP in the repair of large‐size bone defects.